Topographic Analysis of Landing Areas of Apollo Moon Missions - Amathes, Pyrrhon; Christodoulides, Paul (My University, 2017)
The Apollo program was NASA’s (National Aeronautics and Space Administration) human spaceflight program, accomplishing landing of the first humans on the Moon from 1969 to 1972. Ever since there have been scientific and public questions about its legitimacy and claims that the associated Moon landings were staged by NASA and/or other organizations. In this paper we examine a number of the Apollo mission images through (i) a comparison with simulated views of Google Earth (Moon) and (ii) a photographic analysis of some of their features using Photoshop®. The functionality of latitude, longitude, elevation and elevation profile of Google Earth is addressed by means of a comparison with other available programs possessing the same features like NASA’s Moon Trek and Alcyone Lunar Calculator. The topographic analysis through Google Moon simulations indicate that the landscapes in Apollo mission images used were inaccurate presentations of reality and there are incorrect elevations and serious land feature omissions. Moreover, the Photoshop® analysis shows conclusively that images were staged, manipulated or altered.
Keywords: Apollo missions; Moon landings; Photoshop; Google Earth (Moon); Lunar topography